Epistemic Exploitation - Berenstain, Nora (Ergo, an Open Access Journal of Philosophy, 2016)
Epistemic exploitation occurs when privileged persons compel marginalized persons to educate them about the nature of their oppression. I argue that epistemic exploitation is marked by unrecognized, uncompensated, emotionally taxing, coerced epistemic labor. The coercive and exploitative aspects of the phenomenon are exemplified by the unpaid nature of the educational labor and its associated opportunity costs, the double bind that marginalized persons must navigate when faced with the demand to educate, and the need for additional labor created by the default skepticism of the privileged. I explore the connections between epistemic exploitation and the two varieties of epistemic injustice that Fricker (2007) identifies, testimonial and hermeneutical injustice. I situate epistemic exploitation within Dotson’s (2012; 2014) framework of epistemic oppression, and I address the role that epistemic exploitation plays in maintaining active ignorance and upholding dominant epistemic frameworks.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; discours dominant; exploitation épistémique; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; inégalités; oppression épistémique; philosophie; privilèges; sciences humaines; systèmes d'oppressions; thématiques; travail; violences; éthique

Traite, prostitution, inégalité - MacKinnon, Catharine A. (Collection Mobilisations, 2014)
De nos jours, il n'y a pas plus de prise de position favorable à la traite des êtres humains à des fins d'exploitation sexuelle qu'il y a de prise de position publique pour l'esclavage. Il est également très difficile de trouver des partisanes déclarées de l'inégalité… Ce n'est pourtant pas le cas de la prostitution. Certaines personnes sont pour la prostitution. Plus nombreuses sont celles qui considèrent politiquement correct de la tolérer. La plupart présument que, même si elle n'est pas réellement souhaitable, la prostitution est nécessaire, inévitable et sans dommage. Est-ce que la décriminalisation du proxénétisme et la légalisation des maisons closes assureront une plus grande sécurité physique aux personnes prostituées ? Contrairement à la Cour suprême du Canada, la juriste de réputation mondiale, Catharine A. Mac- Kinnon, répond négativement à cette question. Elle soutient que « loin de rendre la vie des prostituées plus sûre, la décriminalisation totale de la prostitution peut même la rendre encore plus dangereuse ». Pour cela, elle s'appuie sur les expériences des pays qui ont légalisé la prostitution et le proxénétisme et sur celles des pays, de plus en plus nombreux, qui décriminalisent les personnes prostituées et pénalisent les clients-prostitueurs ; la stigmatisation liée à l'activité Prostitutionnelle se retourne désormais contre ceux qui en profitent : les prostitueurs et les proxénètes.
Keywords: 2000 à aujourd'hui; amérique du nord; amériques; approches et analyses; canada; care; corps; cours; discipline; droits des femmes*; inégalités; justice sociale; patriarcat; phi2030; philosophie; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; travail; travail du sexe; travail du sexe-prostitution; violences

Life notations of Daisy Sweeney: Reflections of othermothering, musicianship and Montreal - Campbell, Arlene (Université York, 2012)
The life story of Mrs. Daisy Sweeney, an African Canadian native of Montreal, Quebec, helps fill a void in the historical documentation of Montreal Blacks (especially female elders). Of particular significance is her prominence as a music educator and othermother during her life. The current literature on African Canadian othermothering experiences is not synonymous with both White or African American females and inclusion of their voices in academic, as well as mainstream spaces, is virtually non-existent. This dissertation asks: What did it mean to be a first generation 'Negro' working class bilingual female in a largely hostile White francophone Quebec metropolis in the early 20th Century? How can her narratives help shape and inform life history and African Canadian othermothering research? My sojourn with Mrs. Daisy Sweeney referenced African centered epistemology in my conceptual understanding of herself and community mothering. Capturing her conversations meant engaging with multiple methodologies articulated through African oral traditions, life history, archival canons and interdisciplinary inquiries. It is striking to note that there were not only certain tensions associated with memory loss and physical limitations (prompted by the aging process) that destabilized and enriched our 'interactive' communication, but also revealed a rupture and reversal of the participant/researcher dynamic. In spite of blatant racial discrimination that plagued Montreal's Black communities during that time, Daisy Sweeney fulfilled a life-long dream and taught hundreds of children the canon of classical piano for over 50 years. She lived her voice through her music, finding ways to validate her own identity and empowering others in the process. She used the musical stage as her platform to draw invaluable connections between race, gender, language and social class. Daisy Sweeney's generation of othermothers is dying out and, as the carriers of culture, the urgency to tell their stories must be emphasized. The account respects, reclaims and reflects those voices. It is time to write in African Canadian female elders and diversify the exclusionary genre of life history and archival research.
Keywords: 1900-1999; DIG; afro-féminisme; amériques; approches et analyses; discipline; femmes* noires; histoire et politique; maternité; montréal; musique; mémoires/thèses; philosophie; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; travail

BLOOD UNDER THE BRIDGE: REFLECTIONS ON “THINKING SEX” - Rubin, Gayle (GLQ: A Journal of Lesbian and Gay Studies, 2011)
This article reflects on the intellectual and political circumstances of the publication of Gayle Rubin's 1984 essay “Thinking Sex: Notes for a Radical Theory of the Politics of Sexuality.” In particular, the article considers the context of the feminist “sex wars” of the late 1970s and early 1980s, offering a detailed account of several of the period's key events, publications, and debates. The article also reflects on the relation between this moment in the history of feminism and the history of GLBT and queer scholarship over the past several decades.
Keywords: 1900-1999; 1960-1969; 1970-1979; LGBTQIA2+; amériques; approches et analyses; cours; discipline; discours dominant; féminisme pro-sexe; histoire et politique; militance; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sex wars; soc2014; systèmes d'oppressions; thématiques; travail; violences; états-unis; études de genres

Mais oui c'est un travail!: penser le travail du sexe au-delà de la victimisation - Parent, Colette; Bruckert, Chris; Corriveau, Patrice; Nengeh Mensah, Maria; Toupin, Louise (Collection Problèmes sociaux & interventions sociales, 2010)
La question du travail du sexe fait toujours, aujourd’hui, l’objet de polémiques où le moralisme et les bons sentiments prévalent sur la discussion ouverte. La traite des femmes pour fins de « prostitution » et leur vulnérabilité physique face à la violence et à l’homicide débouchent souvent sur des demandes de répression accrue, et ce sont les travailleuses du sexe qui font les frais de ces discours prohibitionnistes et moralisateurs. Soucieux de véhiculer auprès d’un large public une vision différente de la « prostitution » dans le respect des travailleuses du sexe et de remettre en question les bases du message néo-abolitionniste qui présente ces dernières essentiellement comme des victimes de souteneurs ou de leur fausse conscience, cinq spécialistes ont entrepris la rédaction collective d’un livre pour démystifier plusieurs préjugés liés au travail du sexe. Sont abordés dans ce livre original les fondements du débat actuel de la « prostitution » comme travail, les différentes réponses des régimes juridiques, la variété de pratiques et d’expertises mises en oeuvre par les femmes elles-mêmes, incluant celles des migrantes illégales, et l’action collective des regroupements qui luttent pour une reconnaissance du travail du sexe. Mais oui c’est un travail ! invite donc à déconstruire certains mythes et stéréotypes, et à étayer la preuve à l’effet qu’il est non seulement possible de défendre la légitimité du travail du sexe tout en luttant contre la violence, mais que cela est nécessaire.
Keywords: 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; canada; care; corps; corps féminin; cours; discipline; phi2030; philosophie; premier cycle; prostitution; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; sexualité; systèmes d'oppressions; thématiques; travail; travail du sexe; travail du sexe-prostitution

Qu'est-ce que le care?: souci des autres, sensibilité, responsabilité - Molinier, Pascale; Laugier, Sandra; Paperman, Patricia (Petite bibliothèque Payot, 2009)
"Apporter une réponse concrète aux besoins des autres, telle est, aujourd'hui, la définition du care, ce concept qui ne relève pas, comme on l'a longtemps cru, du seul souci des autres ni d'une préoccupation spécifiquement féminine, mais d'une question politique cruciale recoupant l'expérience quotidienne de la plupart d'entre nous. Première synthèse sur cette notion d'une très grande ampleur après les travaux fondateurs de Carol Gilligan dans les années 1980 puis de Joan Tronto dans les années 1990, ce livre concerne aussi bien le domaine du travail que ceux du genre, de l'éthique et de la santé."
Keywords: 1900-1999; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; canada; care; cours; discipline; phi4336; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; travail; travail du care

Justice, gender, and the family - Okin, Susan Moller (Basic Books, 1989)
This work is a feminist critique of modern political theory. The author sets out to show how the failure to apply theories of justice to the family not only undermines democratic values but has led to a major crisis over gender-related issues.
Keywords: amériques; approches et analyses; care; discipline; division sexuelle du travail; droit; droits des femmes*; famille; genre; mariage; maternité; militance; patriarcat; philosophie; ressource en ligne; régions géographiques; science politique et droit; sciences humaines; stéréotypes de genre; systèmes d'oppressions; thématiques; travail; états-unis